Multi-perspectives crowdsourcing ecosystem in Malaysia - Norjansalika Janom; Raja Nurul Azhani; Syaripah Ruzaini Syed Aris; Nor Shahniza Kamal Bashah; Noor Habibah Arshad; Muhammad Hakim Nadir (Institute of Advanced Engineering and Science, 2020)
Crowdsourcing has been known as developing industry that able to be used as a platform to get more income and provide opportunity for busineses to conduct their operation in more innovative ways. Crowdsourcing has become an effective way for the companies to offer work opportunity for crowd outside organization to apply their abilities and skills, and receive more money. Under the Malaysian government initiatives called Digital economy, various crowdsourcing efforts and programs have been introduced to catch up with the global development. The ecosystem of crowdsourcing which consists of job provider, platform, micro worker and industry is considered still in a formative stage. Thus, the integration of all these components is not fully discovered and understood yet which, can cause confusion among the crowdsourcing industry players. In order to understand the complex integration of multi perspective micro sourcing ecosystem, the components and its significance priority level need to be identified. In this study, the components that involved in crowdsourcing ecosystem were identified and ranked using analytical hierarchy process (AHP) method. The results can be later used by crowdsourcing industry players to plan more proper crowd sourcing strategic development in Malaysia.